System dynamics modeling of the impact of Internet-of-Things on intelligent urban transportation - Phil Marshall (International Telecommunications Society (ITS), 2015)
Urban transportation systems are at the cusp of a major transformation that capitalizes on the proliferation of the Internet-of-Things (IoT), autonomous and cooperative vehicular and intelligent roadway technologies, advanced traffic management systems, and big data analytics. The benefits of these smart-transportation technologies were investigated using System Dynamics modeling, with particular emphasis towards vehicle sharing, intelligent highway systems, and smart-parking solutions. The modeling results demonstrate that these solutions offer the potential to deliver tremendous opportunities to improve the efficiencies in urban transportation systems. However it is also observed that by improving the overall utility of roadway transportation, it is likely that there will be an increase in roadway usage that potentially negates the benefits that planners are seeking. As a consequence, when smarttransportation technologies are adopted, they must be implemented in conjunction with solutions and incentive plans that encourage the desired commuter behaviors.
Keywords: 330